Respuesta de dos tipos de injerto de cacao y tres tipos de cinta parafina cinta cera polietileno en diferentes fases lunares - Yunga Ortega, Víctor Manuel (2012)
The present research on response of two types of cocoa graft and three types of tape (paraffin wax tape and polyethylene) in different phases of the moon, was held at the Black Río Site located thirteen km road Pasaje -Paccha, with an altitude of twenty- eightmetersabove sea level, belonging to the parish La Victoria, Santa Rosa county, province of El Oro. He raised the following objectives: 1. Establish the best type of graft and ribbon tie in the cultivation of cocoa, 2.To determine the proper time for grafting cacao, and 3. Perform economic analysis of treatments.The substrate for filling bags of polyethylene of ten per eight centimeters had a ratio of two parts of fresh soil, a sandy, rice chaff average, half of humus were used to disinfect and one percent formaldehyde, coating by seven days and turning it every forty- eight hours.Later planting was conducted using nine hundred sixty seeds classifying by size and took large ones, removing the ends to be small and misshapen head was discarded and the rice submerged in water for five minutes.We proceeded to the grafting, within sixty days after planting, taking into account the lunar phases and the different types of tape used.Statistical analysis revealed that the treatments differ significantly, each of the moon phases studied graft averages highlighting barb on the yolk, adding the nature of ribbon used to tie the pattern graft gave significant differences.On the other hand in the combined analysis of variance, it was found that the moon phases by treatment interaction was highly significant established that the full moon is very favorable for the activation of buds, number of shoots, shoot height and in grafts (yolk and spike) more notoriety for grafting pick. And the new moon favors the ignition and emission leaves grafts (yolk, plectrum) being more evident in the graft scion.The best economic benefit for bud grafts and barbed tape was with wax by the labor savings it provides.